SAT math - Number and Operations
How can we find the result of the following expression:
(2-(3-(1-(2-(4-3)))))-(2-(3-(1-(2-(4+3)))))
Thanks!:o:o
Printable View
SAT math - Number and Operations
How can we find the result of the following expression:
(2-(3-(1-(2-(4-3)))))-(2-(3-(1-(2-(4+3)))))
Thanks!:o:o
Brynlee you have to work from the innermost to the outermost parentheses
(2-(3-(1-(2-(4-3)))))=(2-(3-(1-(2-(-1)))))=(2-(3-(1-(2+1))))=(2-(3-(1-3)))=(2-(3-(-2)))=(2-(3+2))=(2-5)=-3
and the rightmost expression is
(2-(3-(1-(2-(4+3)))))=(2-(3-(1-(2-(7)))))=(2-(3-(1-(-5))))=(2-(3-(1+5)))=(2-(3-(6)))=(2-(-3))=(2+3)=5
So the final result is (-3)-5=-8
Hope these help!!;);)
Thanks miranda!:)